Legal Review of the Use of Smart Contracts in Cyber Notary Services with Blockchain Security Based on the Perspective of UUJN and UU ITE - Sari, Novita; Kahar, Sarifa Amina; Fahreza, Zumali; Rishan, Idul (Sultan Agung Notary Law Review, 2024)
This study examines the application of smart contracts in cyber notary services in Indonesia that use blockchain security and then conducts an in-depth analysis of regulations that accommodate their relationship with UUJN and UU ITE. The concept of smart contracts is based on the need for fast, cheap, objective, real-time and online exchange of goods and services, so that it is widely used in electronic transactions. Basically, electronic contracts are the same as contracts in general, the only difference is that electronic contracts are made through an electronic system while conventional contracts are made directly in oral or written form, as well as smart contracts that are present through an electronic program in the field of contracts based on the principle of freedom of contract regulated in the third book of the Civil Code, and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions or the ITE Law, in addition to its implementation regulated in Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions or PP PSTE and Government Regulation Number 80 of 2019 concerning Trade through electronic systems hereinafter referred to as PP PMSE. Smart Contract technology with blockchain security is undeniably used in the notary profession, where the notary's authority is stated in Article 15 of the Notary Law that the notary is authorized to make authentic deeds, but there are problems in implementing smart contracts in making authentic deeds with blockchain security, namely in the legal certainty regarding the validity and strength of the authentic deed. So that regulations are needed that regulate the application of smart contracts in making authentic deeds with blockchain security in cyber notary services and adequate technology and regulations are needed to support this smart contract service.